High-molecular organic-inorganic composite cementing material for cemented filling of tailings and preparation method of high-molecular organic-inorganic composite cementing material
By using polymer organic and inorganic composite cementing materials in tailing sand cementing filling, water-soluble organic polymer reacts with slag micropowder to form an organic-inorganic interpenetrating network structure, the problems of poor cementing performance and high cost are solved, and the cementing and filling effect with high strength, low cost and environmental protection is achieved.
Patent Information
- Application Number
- CN202411691691.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-04-25
AI Technical Summary
Existing cement as tailings cementing filling materials has problems such as poor cementing performance, high cost and environmental pollution, especially in the treatment of sulfur-containing tailings and ultra-fine tailings.
The polymer organic and inorganic composite gelling material is used to react with slag micropowder or fly ash, and the C-O-Si/Al organic-inorganic interpenetrating network structure is formed, which improves the adhesion, flexibility and corrosion resistance of the gelling material, and at the same time reduces the amount of slag micropowder and cement.
While maintaining their respective advantages, it has achieved a gelling system with better performance, which has reduced the amount of metallurgical slag and cement in the system, increased the strength of cemented filler, and reduced environmental pollution.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of underground mine filling, and in particular relates to a high-molecular organic-inorganic composite gelling material for tailings cementing filling and a preparation method thereof. Background Art Tailings cementation filling is an important means and supporting technology for green mine construction and waste-free mine construction. It makes efficient use of mine solid waste, eliminates tailings ponds and manages goaf areas, forming a mining method with high recovery rate and low depletion rate. Its advantages in environmental protection and economic benefits are becoming more and more significant. Filling cementitious materials are one of the key contents of filling mining optimization design, which directly affects the filling cost and the stability of the mining site. Metal mines widely use cement as a cementing material for tailings cementing filling. However, cement as a cementing material has poor cementing and curing performance for sulfur-containing tailings and ultra-fine tailings. On the other hand, the cost of cement remains high, accounting for more than half of the comprehensive cost of underground filling. At the same time, the large amount of carbon dioxide emissions (about 0.9 tons of CO2 are emitted for every ton of filling slurry produced). The large-scale use of cement will undoubtedly cause a serious burden on the ecological environment. The research on low-cost, high-performance, and environmentally friendly cementing materials has become an important topic for cementing paste filling. In recent years, with the deepening of the development concepts of "waste-free mines" and "green mines" and the continuous advancement of resource recycling technology, the use of slag powder, fly ash and other waste or by-products rich in volcanic ash activity as the main raw materials for the preparation of underground filling cementitious materials has become a hot spot in the field of underground filling engineering. These materials can not only effectively reduce the discharge of waste in the mining process and reduce the damage to the natural environment, but also provide good cementing performance and stability in underground filling operations through their volcanic ash reaction characteristics, which is of great significance for ensuring mine safety and improving resource recovery rate. However, as a key raw material that has long been used at high value in the cement concrete industry, slag has become a valuable resource in short supply in most parts of the country due to its unique physical and chemical properties and excellent performance. With the continuous advancement of infrastructure construction and the continuous growth of cement production demand, the market demand for slag has increased sharply, which has directly led to the year-on-year increase in its raw material costs. Summary of the invention
[0005] In order to further reduce the cost of underground filling, the present invention provides a polymer organic-inorganic composite cementitious material for tailings cementing filling and a preparation method thereof, so as to reduce the amount of slag powder and cement used in tailings cementing filling. In the process of introducing a water-soluble organic polymer material into the cementitious material for reaction, the polar hydrophilic group in the water-soluble organic polymer will undergo polycondensation bonding with the hydroxyl groups in the silicon (aluminum) oxygen tetrahedron of the slag powder or fly ash to form a CO-Si / Al organic-inorganic interpenetrating network structure, wherein the polymer organic component generally has good adhesion, flexibility and corrosion resistance, while the inorganic material provides high strength, hardness and stability. This composite method enables the composite cementitious material to complement each other's shortcomings while maintaining their respective advantages, forming a cementitious system with better performance, while reducing the amount of metallurgical slag and cement used in the system, and improving the strength of the cementitious filling body. In order to achieve the above technical objectives, the present invention adopts the following technical solutions: 1. A high molecular weight organic-inorganic composite gelling material for tailings cementation filling, characterized in that the composite gelling material is composed of organic high molecular weight material and inorganic material, the organic high molecular weight material accounts for 0.5-3% of the total mass percentage of the composite gelling material, wherein: (1) The inorganic raw materials of the composite cementitious material are composed of the following components: slag powder, silica fume, and active activator; (2) The organic polymer raw materials of the composite gelling material are composed of one or more of the following components, including: polyacrylamide, polyacrylic acid, and polyvinyl alcohol. 2. An organic-inorganic composite gelling material for tailings cementation filling according to claim 1, characterized in that the polyacrylic acid in the organic raw materials of the composite gelling material is liquid, and polyacrylamide and polyvinyl alcohol are powdered solids. 3. The organic-inorganic composite cementitious material for tailings cementing filling according to claim 1, characterized in that the specific surface area of the slag powder is ≥400m 2 / kg, the 7-day and 28-day activity indexes are ≥70% and 95% respectively, and the Al2O3 content is >11%, which accounts for 50-90wt% of the mass percentage of the composite cementitious material. 4. An organic-inorganic composite cementitious material for tailings cementing filling according to claim 1, characterized in that the active stimulant raw material components are gypsum and cement clinker, and both account for 5 to 30wt% of the mass percentage of the composite cementitious material. 5. A cementing powder for sulfur-containing tailings according to claim 3, characterized in that the desulfurized gypsum has an attached water content and a chloride ion content of ≤12% and 300 mg / kg, respectively, and a calcium sulfate dihydrate (CaSO4·2H2O) content of ≥90%. 6. The cement powder for sulfur-containing tailings according to claim 3, characterized in that the specific surface area of the cement clinker is ≥300m 2 / kg, 28d flexural and compressive strengths are ≥6.5MPa and 42.5MPa respectively. 7. A method for preparing an organic-inorganic composite cementitious material for tailings cementation filling, characterized in that it comprises the following steps: (1) weighing slag powder, silica fume, desulfurized gypsum and cement clinker according to a certain mass ratio, mixing, stirring and grinding to obtain an inorganic part of a composite cementitious material; (2) Weighing a certain amount of organic polymer material, adding appropriate amount of water and heating in a water bath to prepare an organic polymer solution with a concentration of 50%, and standing for standby to obtain the organic part of the composite gelling material; (3) When performing the filling operation, the above (1) and (2) are stirred evenly to obtain a high molecular weight organic composite cementitious material, and the composite cementitious material is mixed with tailings in a dry weight ratio of 1:6-16, the water content of the organic solution is included in the total water consumption, and water is added to prepare a cementitious filling slurry with a mass concentration of 68-72%. 8. A method for preparing a high molecular organic-inorganic composite cementitious material for tailings cementing filling based on claim 7, characterized in that the tailings include ultrafine tailings with a mass percentage content of -200 mesh particles>70%, and sulfur-containing tailings with a sulfur content>5% in the chemical composition. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Example 1
[0020] (1) 1000 g of the inorganic part of the composite cementitious material is prepared according to the following mass percentages, wherein the inorganic part of the cementitious material accounts for 3 wt% of the mass percentage of the composite cementitious material; the inorganic part of the cementitious material comprises, by mass percentage, 67 wt% of slag powder, 3 wt% of silica fume, and 30 wt% of an active activator; the active activator comprises silicate cement and desulfurized gypsum, and the mass ratio thereof is 3:2.
[0020] (2) The organic part of the composite cementitious material is prepared according to the following mass ratio. 50 g of polyvinyl alcohol powder is weighed and placed in a beaker. 50 ml of ultrapure water is added. The beaker is placed in a constant temperature magnetic stirrer for stirring and heating. The water temperature is maintained at 95±1°C. After the polyvinyl alcohol solid is completely dissolved, the beaker is taken out and sealed with plastic wrap to obtain 100 g of a polyvinyl alcohol solution with a concentration of 50%. The solution is allowed to stand for use. The water content of the solution is included in the total water content.
[0022] (3) Weighing 48.6 g and 785.7 g of the organic and inorganic parts of the composite cementitious materials prepared in (1) and (2) above, respectively, and mixing them with 8.1 kg of a 70% concentration of tailings slurry, wherein the mass of the composite cementitious materials accounts for 12.5% of the dry weight of the sand in the tailings slurry, that is, the cement-slurry ratio is 1:7, adding 77.9 g of water to adjust the mass concentration of the mixed slurry to 72%, and stirring evenly to obtain a tailings cementitious filling material;
[0023] (4) The tailings cementing filling material prepared in (3) above is poured into a 7.07 mm × 7.07 mm × 7.07 mm triple ABS test mold, and then the test mold is placed in a standard curing box with a temperature of 20 ± 2 ° C and a relative humidity of 95%. After hardening, the mold is removed and the test block is continued to be placed in the standard curing box for curing. When the specified age is reached, the test block is taken out and the compressive strength test is carried out according to the "Standard for Test Methods for Basic Properties of Building Mortar" (JGJ / T70-2009). Example 2
[0020] (1) 1000 g of the inorganic part of the composite cementitious material is prepared according to the following mass percentages, wherein the inorganic part of the cementitious material accounts for 2 wt% of the mass percentage of the composite cementitious material; the inorganic part of the cementitious material comprises, by mass percentage, 67 wt% of slag powder, 3 wt% of silica fume, and 30 wt% of an active activator; the active activator comprises silicate cement and desulfurized gypsum, and the mass ratio thereof is 3:2
[0020] (2) The organic part of the composite cementitious material is prepared according to the following mass ratio. 50 g of polyvinyl alcohol powder is weighed and placed in a beaker. 50 ml of ultrapure water is added. The beaker is placed in a constant temperature magnetic stirrer for stirring and heating. The water temperature is maintained at 95±1°C. After the polyvinyl alcohol solid is completely dissolved, the beaker is taken out and sealed with plastic wrap to obtain 100 g of a polyvinyl alcohol solution with a concentration of 50%. The solution is allowed to stand for use. The water content of the solution is included in the total water content.
[0022] (3) Weighing 32.4 g and 793.8 g of the organic and inorganic parts of the composite cementitious materials prepared in (1) and (2) above, respectively, and mixing them with 8.1 kg of a 70% concentration of tailings slurry, wherein the mass of the composite cementitious materials accounts for 12.5% of the dry weight of the sand in the tailings slurry, that is, the cement-slurry ratio is 1:7, adding 81.9 g of water to adjust the mass concentration of the mixed slurry to 72%, and stirring evenly to obtain a tailings cementitious filling material;
[0023] (4) The tailings cementing filling material prepared in (3) above is poured into a 7.07 mm × 7.07 mm × 7.07 mm triple ABS test mold, and then the test mold is placed in a standard curing box with a temperature of 20 ± 2 ° C and a relative humidity of 95%. After hardening, the mold is removed and the test block is continued to be placed in the standard curing box for curing. When the specified age is reached, the test block is taken out and the compressive strength test is carried out according to the "Standard for Test Methods for Basic Properties of Building Mortar" (JGJ / T70-2009). Example 3
[0020] (1) 1000 g of the inorganic part of the composite cementitious material is prepared according to the following mass percentages, wherein the inorganic part of the cementitious material accounts for 1 wt% of the mass percentage of the composite cementitious material; the inorganic part of the cementitious material comprises, by mass percentage, 67 wt% of slag powder, 3 wt% of silica fume, and 30 wt% of an active activator; the active activator comprises silicate cement and desulfurized gypsum, and the mass ratio thereof is 3:2.
[0020] (2) The organic part of the composite cementitious material is prepared according to the following mass ratio. 50 g of polyvinyl alcohol powder is weighed and placed in a beaker. 50 ml of ultrapure water is added. The beaker is placed in a constant temperature magnetic stirrer for stirring and heating. The water temperature is maintained at 95±1°C. After the polyvinyl alcohol solid is completely dissolved, the beaker is taken out and sealed with plastic wrap to obtain 100 g of a polyvinyl alcohol solution with a concentration of 50%. The solution is allowed to stand for use. The water content of the solution is included in the total water content.
[0022] (3) Weighing 16.2 g and 801.9 g of the organic and inorganic parts of the composite cementitious materials prepared in (1) and (2) above, respectively, and mixing them with 8.1 kg of a 70% concentration of tailings slurry, wherein the mass of the composite cementitious materials accounts for 12.5% of the dry weight of the sand in the tailings slurry, that is, the cement-slurry ratio is 1:7, adding 86.0 g of water to adjust the mass concentration of the mixed slurry to 72%, and stirring evenly to obtain a tailings cementitious filling material;
[0023] (4) The tailings cementing filling material prepared in (3) above is poured into a 7.07 mm × 7.07 mm × 7.07 mm triple ABS test mold, and then the test mold is placed in a standard curing box with a temperature of 20 ± 2 ° C and a relative humidity of 95%. After hardening, the mold is removed and the test block is continued to be placed in the standard curing box for curing. When the specified age is reached, the test block is taken out and the compressive strength test is carried out according to the "Standard for Test Methods for Basic Properties of Building Mortar" (JGJ / T70-2009). Comparative Example 1
[0044] (1) 1000 g of inorganic cementitious material is prepared according to the following mass percentages, wherein the inorganic cementitious material comprises, by mass percentage, 67 wt% of slag powder, 3 wt% of silica fume, and 30 wt% of an active activator; the active activator comprises silicate cement and desulfurized gypsum, and the mass ratio thereof is 3:2
[0022] (2) Weigh 81 g of the inorganic cementitious material prepared in (1) above, mix it with 8.1 kg of a 70% concentration of tailings slurry, wherein the mass of the inorganic cementitious material accounts for 12.5% of the dry weight of the sand in the tailings slurry, that is, the cement-slurry ratio is 1:7, add 90 g of water to adjust the mass concentration of the mixed slurry to 72%, and stir evenly to obtain a tailings cementitious filling material;
[0045] (2) The prepared sulfur-containing tailings cementing filling material is poured into a 7.07 mm × 7.07 mm × 7.07 mm triple ABS test mold, and then the test mold is placed in a standard curing box with a temperature of 20 ± 2 ° C and a relative humidity of 95%. After hardening, the mold is removed and the test block is continued to be placed in the standard curing box for curing. When the specified age is reached, the test block is taken out and the compressive strength test is carried out according to the "Standard for Test Methods for Basic Properties of Building Mortar" (JGJ / T70-2009). BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 The compressive strength bar graph of the test blocks prepared in Comparative Example 1 and Examples 1 to 3; Figure 2 This is the SEM image of the test piece of Comparative Example 1 cured for 28 days; Figure 3 This is a scanning electron microscope image of the test piece cured for 28 days in Example 1; Figure 4 This is a scanning electron microscope image of the test block cured for 28 days in Example 2.
Claims
1. A high molecular weight organic-inorganic composite cementitious material for tailings cementation filling, characterized in that: The composite gelling material is composed of organic polymer materials and inorganic materials, and the organic polymer material accounts for 0.5-3% of the total mass percentage of the composite gelling material, of which: (1) The inorganic raw materials of the composite cementitious material are composed of the following components, calculated by weight percentage: 65-94 wt% of slag powder, 1-5 wt% of silica fume, and 5-30 wt% of an active activator, the sum of the percentages of the raw materials being 100%; (2) The organic polymer raw materials of the composite gelling material are composed of one or more of the following components, including: polyacrylamide, polyacrylic acid, and polyvinyl alcohol.
2. The high molecular weight organic-inorganic composite cementitious material for tailings cementation filling according to claim 1, characterized in that The polyacrylic acid in the organic raw materials of the composite gelling material is liquid, and the polyacrylamide and polyvinyl alcohol are powdered solids.
3. The organic-inorganic composite cementitious material for tailings cementation filling according to claim 1, characterized in that The specific surface area of the slag powder is ≥400m 2 / kg, the 7-day and 28-day activity indexes are ≥70% and 95% respectively, and the Al2O3 content is >11%, which accounts for 50-90wt% of the mass percentage of the composite cementitious material.
4. The high molecular weight organic-inorganic composite cementitious material for tailings cementation filling according to claim 1, characterized in that The active activator raw material components are desulfurized gypsum and cement clinker, and both account for 5-30wt% of the mass percentage of the composite cementitious material.
5. The high molecular weight organic-inorganic composite cementitious material for tailings cementation filling according to claim 4, characterized in that The attached water content and chloride ion content of the desulfurized gypsum are ≤12% and 300 mg / kg respectively, and the content of calcium sulfate dihydrate (CaSO4·2H2O) is ≥90%.
6. The high molecular weight organic-inorganic composite cementitious material for tailings cementation filling according to claim 4, characterized in that The specific surface area of the cement clinker is ≥300m 2 / kg, 28d flexural and compressive strengths are ≥6.5MPa and 42.5MPa respectively.
7. A method for preparing a polymer organic-inorganic composite cementitious material for tailings cementation filling, characterized in that: The following steps are involved: (1) weighing slag powder, silica fume, desulfurized gypsum and cement clinker according to a certain mass ratio, mixing, stirring and grinding to obtain an inorganic part of a composite cementitious material; (2) Weighing a certain amount of organic polymer material, adding appropriate amount of water and heating in a water bath to prepare an organic polymer solution with a concentration of 50%, and standing for standby to obtain the organic part of the composite gelling material; (3) When performing the filling operation, the above (1) and (2) are stirred evenly to obtain a high molecular weight organic composite cementitious material, and the composite cementitious material is mixed with tailings in a dry weight ratio of 1:6-16, the water content of the organic solution is included in the total water consumption, and water is added to prepare a cementitious filling slurry with a mass concentration of 68-72%.
8. The method for preparing a high molecular weight organic-inorganic composite cementitious material for tailings cementation filling according to claim 7, characterized in that: The tailings include ultrafine tailings with a mass percentage of -200 mesh particles greater than 70%, and sulfur-containing tailings with a chemical composition containing sulfur greater than 5%.